Students’ Perception of the Game of Football in Physical Education Learning at the Junior High School Level of Pemulutan Sub-District - Alhamdani, Yusuf; Kristina, Putri Cicilia; Putri, Siti Ayu Risma (Journal of Social Work and Science Education, 2023)
This study aims to determine students’ perceptions of football games in physical education learning at the junior high school level. Based on (1) students’ perception of knowledge about the game of soccer, (2) perception of the teacher’s teaching style, (3) perception of the media used is easy to use. This research is descriptive quantitative research. The results of this study showed that (1) students’ perception of knowledge about the game of soccer obtained a score of 86.7% with a very good category, (2) the perception of the teacher’s teaching style obtained a score of 82.50% with a good category, (3) perception of the media used obtained a value of 80% with a good category, (4) Student perceptions of the need for the development of football game models in physical education learning obtained a score of 95% with a very positive category. The results of this study show that students’ perceptions of the development of football games in physical education learning at the junior high school level are positive, for that it is necessary to develop football games in physical education learning in order to create innovative and varied learning.